2019
DOI: 10.1039/c8ra10185j
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plasma-assisted silicon nanoparticles: cytotoxic, molecular, and numerical responses against cancer cells

Abstract: Silicon nanoparticles (SiNPs), which have a special place in material science due to their strong luminescent property and wide applicability in various physicochemical arenas synthesised via a microwave plasma-assisted process using an argon–silane mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Microwave plasma-assisted silicon nanoparticles were shown to be cytotoxic and to have molecular and numerical responses against cancer cells 54 . Silver nanoparticles and earthworm combinations mediated anti-proliferative activity at increasing concentration as revealed by DNA analysis of Hep-G2 cells 55 , 56 . In accordance to our present findings were Amorphophallus paeoniifolius peels ZnO NP inducing cancer cell apoptosis at higher concentrations 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Microwave plasma-assisted silicon nanoparticles were shown to be cytotoxic and to have molecular and numerical responses against cancer cells 54 . Silver nanoparticles and earthworm combinations mediated anti-proliferative activity at increasing concentration as revealed by DNA analysis of Hep-G2 cells 55 , 56 . In accordance to our present findings were Amorphophallus paeoniifolius peels ZnO NP inducing cancer cell apoptosis at higher concentrations 57 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the FESEM images of all the nanoparticles have shown the size <50nm of all the nanoparticles. Whereas DLS has shown that most amorphous nanoparticles because of rapidly agglomeration due to their high surface area and reactivity, resulting in differences in primary and secondary size (27,28). So that particle size reached above 1000 nm, whereas for B-E samples, the mean particle size was <50 nm.…”
Section: Characterization Of Sio 2 Npsmentioning
confidence: 99%
“…The electrostatic interaction between the nanocomposite and the cell lines may have caused a reduction in the cytotoxicity effects, resulting in a lower rate of death with extended incubation time (32).The nonspeci c surface reactivity had a hatching rate that was proportional to the concentration. The CeO 2 /ZnO/GO hybrid nanocomposite demonstrated stronger cytotoxicity effects against HeLa cells than previously reported CeO 2 nanoparticles (33,34) when tested for anticancer activities.The %cell inhibition rate induced by interacting cerium oxide nanoparticles, zinc oxide NPs and the hybrids against various cancer cell lines was compared to previously published results and is summarized in Table 1. The induced % cell death upon interaction of CeO 2 /ZnO/GO hybrid with HeLa cell line was further subject to qualitative analysis using AO/EB Dual Staining study which was performed at different concentrations such as 1000µg/ml, 500µg/ml and 250µg/ml.…”
Section: In-vitro Cytotoxicity Evaluation Of Ceo2/zno/go and Ceo2/cddp-zno/go Systemson Hela Cells And Normal Cellsmentioning
confidence: 62%